The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4012/dmj.2014-195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porous-hydroxyapatite incorporated into glass-ionomer sealants

Abstract: The purpose of the present study was to evaluate the mechanical and chemical properties of a novel glass ionomer cement for use as a pit and fissure sealant containing a porous hydroxyapatite, namely, apatite ionomer cement (AIC). Control sealant samples were used Fuji III (GIC-S). The experiment sealant samples (AIC-S) consisted of porous spherical hydroxyapatite (HApS) particles added at 28 wt% to GIC-S powder. The GIC-S and AIC-S samples were evaluated through mechanical strength measurements, scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…The AIC specimens in our previous studies [20,21,22,23,24] were made by reducing GIC powder and adding HAp powder instead. Because fluoride is contained in the GIC glass powder, it was not clear why the AIC had superior fluoride release properties in spite of a decrease in the amount of GIC powder.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The AIC specimens in our previous studies [20,21,22,23,24] were made by reducing GIC powder and adding HAp powder instead. Because fluoride is contained in the GIC glass powder, it was not clear why the AIC had superior fluoride release properties in spite of a decrease in the amount of GIC powder.…”
Section: Discussionmentioning
confidence: 99%
“…Arita et al demonstrated that porous HAp made by grinding HAp with columnar crystal shapes using an automatic ball mill is suitable for use in dental restorative AIC formulations [21]. In our study, a commercial porous HAp (HApS) was selected because of its low cost, and because it can produce an AIC with applications as a restorative and sealing material [23,24]. However, an AIC including this spherical, porous HApS has not yet been compared with materials made with HAp powders with other morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations